Antioxidant, Antimicrobial, and Photocatalytic Potential of Cobalt Fluoride (CoF2) Nanoparticles - Jamshid Khan; Hameed Ullah; Riaz Ullah; Muhammad Sajjad; Khalid Hussain Thebo; Amal Alotaibi; Muhammad Zahoor; Nadia Bukhari; H. C. Ananda Murthy (Adsorption Science & Technology)
Herein, CoF2 nanoparticles (NPs) are prepared by simple coprecipitation method and are characterized by various techniques, i.e., XRD, SEM/EDX, FTIR, and UV/Vis, for their structure identification. As-prepared nanostructures were used as photocatalyst, as antioxidant, and as antimicrobial agent. The degradation studies of the prepared samples were carried out for specific time for the degradation of methylene blue (MLB) dye under a UV/visible spectrophotometer to determine decolorization and change in concentration of MLB with respect to time. The antibacterial activity against Escherichia coli (E. coli) and Bacillus subtilis (B. subtilis) was measured by well diffusion and serial dilution method to determine their efficiency against these two bacteria, through a dose-dependent method. The antibacterial activity was further confirmed against the experimental bacteria through calculation of minimum inhibition concentration (MIC). The antioxidant activity (radical scavenging activity) of the prepared CoF2 NPs was also assessed.